Antara Salafi dan Sufi: Tasawuf menurut Ibn Taimiyyah dan al-Qusyairi - Maghribi, Hamdan; Hidayah, Alfina (Universitas Darussalam Gontor, 2023)
This article discusses two sects that are often contrasted: Salafi and Sūfī. It focuses on the views of Ibn Taimiyyah al-Harrānī as a representative of Salafi and ‘Abd al-Karīm al-Qusyairī of Sūfī-sunnī on Sufism. By analyzing the works of Ibn Taimiyyah and al-Qusyairī on Sufism, this article explores Ibn Taimiyah’s critical notes on al-Qusyairi's views on Sufism. Ibn Taimiyyah wrote no less than thirty-eight treatises on Sufism and cited more than forty Sūfī texts in explaining and analyzing his views on Sufism. Al-Qusyairī, on the other hand, describes in detail the Sūfī figures and their views in his Risālah. He also included his Sufistic analyses in Laṭāif al-Ishārāt. Using an interpretative approach and content analysis, this article finds that Ibn Taimiyyah did not reject Sufism. He rejected the practice of Sufism that he thought was not intertwined with the Qur’ān and Sunnah. This is evident from his respect for al-Qusyairī, whom he called al-Syaikh al-Ustāż, and Mutaṣawwifah Ahl al-Kalām, a term of honor within the Ṣūfī order. Nonetheless, Ibn Taimiyyah notes that al-Qusyairī’s quotations in his work are not followed by references and explanations. In explaining the practice of zuhd, al-Qusyairī did not provide examples from the ṣahābah and tābi’īn to strengthen his argument.